2015
DOI: 10.2105/ajph.2015.302672
|View full text |Cite
|
Sign up to set email alerts
|

Support for Policies to Improve the Nutritional Impact of the Supplemental Nutrition Assistance Program in California

Abstract: The Supplemental Nutrition Assistance Program (SNAP) provides a vital buffer against hunger and poverty for 47.6 million Americans. Using 2013 California Dietary Practices Survey data, we assessed support for policies to strengthen the nutritional influence of SNAP. Among SNAP participants, support ranged from 74% to 93% for providing monetary incentives for fruits and vegetables, restricting purchases of sugary beverages, and providing more total benefits. Nonparticipants expressed similar levels of support. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
1
12
1
2
Order By: Relevance
“…13,32,33 In multiple studies a majority of stakeholders, including SNAP participants, have supported restrictions on purchasing sugar-sweetened beverages with SNAP dollars as well as supported the provision of additional SNAP benefits for fruits and vegetables. 13,32,34 Counter to claims that program modifications would be difficult to implement, the Healthy Incentives Pilot showed that changes to SNAP are feasible (most retailers did not find the Healthy Incentives Pilot difficult to operate, and >90% reported no change in checkout time). 35 The vast majority of all food prepared at home is purchased in supermarkets and at other large retailers 36 where electronic point of sale technology is readily available and could be used to implement changes in SNAP policy.…”
Section: Discussionmentioning
confidence: 99%
“…13,32,33 In multiple studies a majority of stakeholders, including SNAP participants, have supported restrictions on purchasing sugar-sweetened beverages with SNAP dollars as well as supported the provision of additional SNAP benefits for fruits and vegetables. 13,32,34 Counter to claims that program modifications would be difficult to implement, the Healthy Incentives Pilot showed that changes to SNAP are feasible (most retailers did not find the Healthy Incentives Pilot difficult to operate, and >90% reported no change in checkout time). 35 The vast majority of all food prepared at home is purchased in supermarkets and at other large retailers 36 where electronic point of sale technology is readily available and could be used to implement changes in SNAP policy.…”
Section: Discussionmentioning
confidence: 99%
“…If program perceptions influence the efficacy of programs like SNAP to ameliorate socioeconomic health disparities, then perhaps policy makers will be encouraged to further prioritize the perspective of social program participants. For example, while some stakeholders have proposed restricting food purchases considered to be unhealthy (Leung et al 2015b), this may not result in positive mental health outcomes if such restrictions perpetuate stigma among program participants (Barnhill & King 2013).…”
Section: Resultsmentioning
confidence: 99%
“…1519 The results of this and other studies have shown that most SNAP participants support removing sugary beverages from the program, particularly if paired with incentives for healthful food. 9,10,20,21 …”
Section: Discussionmentioning
confidence: 99%